Antineoplastic drug occupational exposure: a new integrated approach to evaluate exposure and early genotoxic and cytotoxic effects by no-invasive Buccal Micronucleus Cytome Assay biomarker. (November 2019) - Ursini, C.L.; Omodeo Salè, E.; Fresegna, A.M.; Ciervo, A.; Jemos, C.; Maiello, R.; Buresti, G.; Colosio, C.; Rubino, F.M.; Mandić-Rajčević, Stefan; Chiarella, P.; Carbonari, D.; et al.
Highlights: Surface contamination by GEM and 5-FU in 68% and 42% of wipes/swaps respectively. GEM deposition on workers' pads. Higher induction of geno-cytotoxicity on administrators by BMCyt assay. XRCC1 399 polymorphism could be a susceptibility factor for MN in buccal cells. Abstract: Health-care personnel handling antineoplastic drugs could be at risk for adverse health effects. We aimed to evaluate genotoxic and cytotoxic effects of antineoplastic drug exposure of personnel preparing and administering such drugs in three Oncology Hospitals in Italy enrolling 42 exposed subjects and 53 controls. Furthermore, we aimed to study the possible influence of XRCC1 and hOGG1 DNA repair genes polymorphisms on genotoxicity induced on buccal cells. We performed workplace and personal monitoring of some drugs and used exposure diary informations to characterize the exposure. Urinary 5-FU metabolite (α-fluoro-β-alanine) was measured. Buccal Micronucleus Cytome (BMCyt) assay was used to evaluate DNA damage and other cellular anomalies. GEM and 5-FU contamination was found in 68% and 42% of wipe/swab samples respectively. GEM deposition was found on workers' pads while no α-fluoro-β-alanine was found. BMCyt-assay showed higher genotoxicity and cytotoxicity on nurses administering antineoplastics than on preparators and controls. Among micronucleus (MN) positive (with MN frequency higher than 1.5‰) exposed subjects, the percentage of those carrying XRCC1 mut/het genotype was higher than in MN positive-controls. Using the sensitive BMCyt assay, we demonstrated that handling antineoplastics still represents a potential occupational health risk for workers that should be better trained/informed regarding such risks.